2016
DOI: 10.1541/ieejjia.5.398
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Control in the Vertical Direction Using Functional Electrical Stimulation

Abstract: In this study, we investigated bilateral control in the vertical direction using functional electrical stimulation (FES). Bilateral control is a remote operation technique that incorporates force feedback. This technology has potential applications in everyday life, including allowing medical doctors to make diagnoses or friends to communicate using tactile sensations when far apart. However, current iterations of this technology require robot arms to be worn. This is undesirable as such arms are heavy, and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In contrast, bilateral control is a control method of sending a command value in bi-direction between a master and a slave. Accordingly, the master can feel the external force applied to the slave, thereby simulating the sensation that the master's body has become the slave [13], [22]. In this study, we used position-symmetrical bilateral control because its control system is simple, stable, and does not require a force sensor [23].…”
Section: Bilateral Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, bilateral control is a control method of sending a command value in bi-direction between a master and a slave. Accordingly, the master can feel the external force applied to the slave, thereby simulating the sensation that the master's body has become the slave [13], [22]. In this study, we used position-symmetrical bilateral control because its control system is simple, stable, and does not require a force sensor [23].…”
Section: Bilateral Controlmentioning
confidence: 99%
“…FES can provide a richer tactile sensation because the deep sensations can be transmitted through it. Thus, we attempted to solve this problem by incorporating FES into the master system [11]- [13].…”
Section: Introductionmentioning
confidence: 99%
“…We propose bilateral control-based imitation learning as a method of using force information [14]- [16]. Bilateral control is a teleoperation method where a human operates the master robot and the slave robot performs tasks in the workspace [17]- [20]. During this period, position synchronization and presentation of the reaction forces are simultaneously executed.…”
Section: Introductionmentioning
confidence: 99%
“…Tamaki et al controlled hands using FES; they showed that it was possible to use hands to help play a musical instrument [13]; they used FES to move their fingers and tried to reproduce the object's gripping motion by performing closed-loop control using a force sensor [14]. Kitamura et al performed bilateral control of an elbow joint using FES [15]. These various studies indicate that FES is useful for control.…”
Section: Introductionmentioning
confidence: 99%